The politics of remembering: Hacking, Ian (1995) Rewriting the soul: Multiple personality and the sciences of memory. Princeton: Princeton University Press (hbk). - Collins, Anthony (PINS-Psychology in Society, 2026)
Although this book is a history written by a philosopher, it is an important work for anyone with an interest in psychotherapies based on the retrieval of repressed memory. Hacking's book emerges in the context of a growing battle in the United States between feminist and other groups wishing to expose the widespread incidence of child sexual abuse, and an opposing camp, organised around the False Memory Syndrome Foundation, which has mobilised legal action against psychotherapists for destroying families by producing false memories of incest and sexual abuse. The aim of this book is not to support one of these positions and attack the other, or even to evaluate their competing arguments, but something rather more subtle and interesting: to try and uncover how ways of thinking about memory and the self developed historically to our current situation where this conflict could occur at all.